A Guide for Using Flight Simulators to Study the Sensory Basis of Long-Distance Migration in Insects - Dreyer, David; Frost, Barrie; Mouritsen, Henrik; Lefèvre, Adrien; Menz, Myles; Warrant, Eric (Frontiers in Behavioral Neuroscience, 2021)
Studying the routes flown by long-distance migratory insects comes with the obvious challenge that the animal's body size and weight is comparably low. This makes it difficult to attach relatively heavy transmitters to these insects in order to monitor their migratory routes (as has been done for instance in several species of migratory birds. However, the rather delicate anatomy of insects can be advantageous for testing their capacity to orient with respect to putative compass cues during indoor experiments under controlled conditions. Almost 20 years ago, Barrie Frost and Henrik Mouritsen developed a flight simulator which enabled them to monitor the heading directions of tethered migratory Monarch butterflies, both indoors and outdoors. The design described in the original paper has been used in many follow-up studies to describe the orientation capacities of mainly diurnal lepidopteran species. Here we present a modification of this flight simulator design that enables studies of nocturnal long-distance migration in moths while allowing controlled magnetic, visual and mechanosensory stimulation. This modified flight simulator has so far been successfully used to study the sensory basis of migration in two European and one Australian migratory noctuid species